Pengaruh Inovasi Produk, Kualitas Produk, Promosi Dan Label Halal Terhadap Keputusan Pembelian Di Donat Kentang Malang (Studi Kasus Pada Anggota Organisasi Ikatan Mahasiswa Mojokerto Area Malang) - Dwi Mayangsari; Rois Arifin; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine and analyze the relationship between product innovation, product quality, promotion and halal label on the level of purchasing decisions on Donat Kentang Malang. This research uses a case study method where data is obtained by distributing questionnaires to selected IMMAM members by purposive sampling. Determination of the number of samples using the Slovin formula and the results obtained were 100 respondents. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results showed that based on the F test and t test there was a simultaneous and partial effect between the variables of product innovation, product quality, promotion and halal label on purchasing decisions at Donat Kentang Malang. Adjusted R Square of 23,5% against the dependent variable, namely the purchase decision can be explained by the product innovation variables (X1), product quality (X2), promotion (X3) and halal label (X4) while 76,5% explained by other variables outside this research model. Keywords: Purchase Decision, Product Innovation, Product Quality, Promotion, Halal Label